2011
DOI: 10.1245/s10434-011-1819-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clinical Risk Score for Patients with Colorectal Liver Metastases Still Useable in the Era of Effective Neoadjuvant Chemotherapy?

Abstract: BackgroundSeveral clinical risk scores (CRSs) for the outcome of patients with colorectal liver metastases have been validated, but not in patients undergoing neoadjuvant chemotherapy. Therefore, this study evaluates the predictive value of these CRSs in this specific group.MethodsBetween January 2000 and December 2008, all patients undergoing a metastasectomy were analyzed and divided into two groups: 193 patients did not receive neoadjuvant chemotherapy (group A), and 159 patients received neoadjuvant chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…Moreover, despite some external validation, these score are based on single-institution cohorts and have not been modified based on newer developments in treatments. Lastly, the variations observed in the OS of patients with similar prognostic scores suggest that other factors may play a role in determining survival after resection of CRLM, most intriguingly patientspecific biological and molecular factors [78] .…”
Section: Clinical Scoring Systemmentioning
confidence: 99%
“…Moreover, despite some external validation, these score are based on single-institution cohorts and have not been modified based on newer developments in treatments. Lastly, the variations observed in the OS of patients with similar prognostic scores suggest that other factors may play a role in determining survival after resection of CRLM, most intriguingly patientspecific biological and molecular factors [78] .…”
Section: Clinical Scoring Systemmentioning
confidence: 99%
“…[15][16][17][18][19][20] However, many of these clinical risk scores were developed using patient data that predated modern chemotherapy, making their application to patients treated with a contemporary multidisciplinary approach controversial. 21,22 Previously, our group and others have reported that improved survival correlates with pathologic response to preoperative chemotherapy, which we proposed as a new outcome end point after resection of CLM.…”
Section: Wwwjcoorgmentioning
confidence: 99%
“…11,12 In this issue of Annals of Surgical Oncology, Ayez et al examine this topic with a detailed analysis of four wellknown scoring systems and the effect of neoadjuvant therapy on their prognostic power. 13 The authors confirm that although all four classification systems effectively stratify risk and survival in patients taken directly to operation, prior treatment with neoadjuvant therapy greatly diminishes their predictive capacity. When scores were calculated before administering neoadjuvant therapy, only one of the four systems maintained significance for predicting disease-free survival and/or disease-specific survival.…”
mentioning
confidence: 69%